1995
DOI: 10.1038/bjc.1995.497
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ras p21, p53 and c-erbB-2 in advanced breast cancer and response to first line hormonal therapy

Abstract: Summary Several oncogenes and tumour-suppressor genes have been identified that may have an important role in the development of human breast carcinoma. Furthermore, some of these gene alterations may be linked to the development of invasion and subsequent metastasis. Alterations in the expression of ras p21, p53 and c-erbB-2 have all been linked to tumours with rapid cellular proliferation. but the evidence that they are of prognostic importance in patients with breast cancer is conflicting. This study explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
1
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(70 citation statements)
references
References 34 publications
5
63
1
1
Order By: Relevance
“…The same negative results were reported in the literature concerning p21 in the only report that dealt with patient age, 6 in all five studies concerning hormone receptor status, 59 -61,87,88 in one of three studies concerning lymph node status, 60 in one of two studies concerning tumor size, 60 in two of six studies concerning Scarff-Bloom grade, 59,60 and in three of six studies concerning p53. 59,61,89 The results were different concerning mitotic activity and in both studies that correlated p21 with mitotic activity. 61,89 p53 was correlated with histologic grade, hormone receptor status, mitotic activity, SPF, Ki-67, and cyclin A.…”
Section: Discussionsupporting
confidence: 55%
“…The same negative results were reported in the literature concerning p21 in the only report that dealt with patient age, 6 in all five studies concerning hormone receptor status, 59 -61,87,88 in one of three studies concerning lymph node status, 60 in one of two studies concerning tumor size, 60 in two of six studies concerning Scarff-Bloom grade, 59,60 and in three of six studies concerning p53. 59,61,89 The results were different concerning mitotic activity and in both studies that correlated p21 with mitotic activity. 61,89 p53 was correlated with histologic grade, hormone receptor status, mitotic activity, SPF, Ki-67, and cyclin A.…”
Section: Discussionsupporting
confidence: 55%
“…However, it has also been concluded that p53 mutation or accumulation predicts poor response to tamoxifen (14,48). The results in the present study demonstrated that the patients with both normal and altered p53 status appear to have a good response to tamoxifen.…”
Section: Discussionsupporting
confidence: 64%
“…Also, survival in patients with stable disease of greater than 6 months duration is similar to that of patients that achieve a PR to treatment (Manni et al, 1989). Others groups studying similar patients defined ÔresponseÕ as CR + PR + SD of more than 6 months duration (Wright et al, 1992;Klijn et al, 1993;Archer et al, 1995;Berns et al, 1995;Elledge et al, 1998), and most demonstrated that overexpression of c-erbB2 reduced the response rate to endocrine therapy in advanced breast cancer.…”
Section: Discussionmentioning
confidence: 96%
“…Two studies reported that c-erbB2 overexpression did not alter response to hormonal therapy (Archer et al, 1995;Elledge et al, 1998). The former was based on fewer than 100 patients and so lacked statistical power.…”
Section: Discussionmentioning
confidence: 99%